Ecological Approach to the Development of Locomotion: Karen Adolph’s Studies on Development - Nishio, Chihiro (Japanese Journal of Ecological Psychology, 2022)
Recent research on infant development investigates the impact of walking acquisition on the development of language and social behavior. Karen Adolph often refers to the relationship between motor development and a wide range of behavioral development as a developmental cascade, noting that motor development can instigate changes in perceptual, cognitive, and social development. This review is an overview of the literature by Adolph, who has been conducting studies on infant motor development, particularly focusing on walking, and examines the key words used in her studies, such as flexibility and experience, variability, and daily environment. Based on the suggestions from these studies, future research regarding an ecological approach to the development of locomotion is discussed.